The Asian economic crisis and Malaysia's responses: Implications for the banking sector - Balakrishnan Parasuraman; Lim, Beatrice; Furuoka, Fumitaka; Catherine Jikunan; Lomay Chiun (Springer India, 2013)
The economic meltdown began in Thailand in July 1997 and spread to other countries in the region, such as Malaysia, Indonesia, the Philippines, and South Korea. This phenomenon was later called the contagion effect. To improve economic foundations, Thailand, Indonesia, and South Korea decided to ask for and received rescue packages from the International Monetary Fund (IMF). However, as the IMF's conditions were very strict, some experts doubted the validity of the IMF's policies.